The graph heuristic with great deluge algorithm to solve the ITC2007 examination timetabling problem - Chuan, Wei Kiat (2014)
Examination timetabling problem involve allocating the exams into a specific or limited number of timeslot and rooms. The produce examination timetable should meet all the hard constraints and achieve the soft constrains as much as possible. In this research, dataset of examination track from second International Timetabling Competition (ITC 2007) will be use. This dataset contains of total of twelve dataset which have different features (i.e. number of room, exam and timeslot). The graph heuristic with great deluge algorithm will be used to solve this problem. We hope that the proposed technique will be able to produce better result than other technique in the literature.